Is the Borneo Palm Oil Plantation Company Categorized in Investment Grade? - Saratian, Eko Tama Putra (Formosa Journal of Sustainable Research, 2024)
This study aims to identify which oil palm plantations in the Kalimantan region are currently entering the replanting stage and which are rated as "investment grade" by Moody's. It also aims to determine how to invest in oil palm plantations that are currently classified as "investment grade" and/or can raise the notch rating through Moody's. Using a case study methodology, this research is qualitative in nature. Purposive sampling was used in this study's participant selection process, and secondary data sources were used to gather data. Moody's rating analysis is the type of data analysis used in this study. To obtain values for the historical ratio assessment and balance sheet factor variables, a spreading assessment of the company's financial statements for the previous three years is conducted. Additionally, an assessment of the industry/market, company, and management variables is conducted, with data for these variables coming from both internal and external companies. financial reports as well as sales reports, annual reports, legality of production reports, and other supporting documentation. Following input and comprehensive study, an assessment of "B1" with a risk category of "Medium Risk" is the result. Plantation enterprises in Kalimantan that engage in replanting are therefore categorized as investment grade or suitable for investment. Some adjustments must be made for the investment level to either minimally rise or fall into the "Low Risk" category to draw in investors